Genealogi Moral Menurut Foucault dan Nietzsche: Beberapa Catatan - Pranowo, Yogie (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
This article shows that what Foucault understands as genealogy is in many ways still in line with Nietzsche, that in terms of the basic concept of genealogy, using history, reveals the Herkunft – the origin of values that will dismantle the assumption of finality. Morality is born in the midst of a chaotic situation that forces individuals to make decisions and in the experience of a fragmented and unstable body. While through Entstethung one can see how the dominations that play behind any value are considered noble, the noble value is not in the hands of an independent subject. But there are also differences, since Foucault calls for the death of the subject, while Nietzsche is not up to that extreme. Another point of difference is that Foucault’s genealogy is practiced in a strict study discipline, wrestling with historical documents and writing down the detailed facts, while Nietzsche does not. The author argues that through Foucault’s thought, one might find a new meaning of the subject, that the subject is not an autonomous entity, but merely a production of power. The appearance of the subject is considered as a result of domination-relationships. In other words, these are the result of a disciplining effort.